Intraoperative hypotension and postoperative delirium in elderly male patients undergoing laryngectomy: a single-center retrospective cohort study - Yiru Wang; Kaizheng Chen; Min Ye; Xia Shen (Brazilian Journal of Anesthesiology)
Background: Postoperative delirium (POD) is a common, transient postoperative cognitive dysfunction in elderly patients. The relationship between POD and intraoperative hypotension remains unclear. This study aims to determine if intraoperative hypotension predicts POD in elderly male patients undergoing laryngectomy. Methods: This study included male patients over 65 years old who underwent laryngectomy between April 2018 and January 2022. The Confusion Assessment Method (CAM) was used to diagnose delirium. Intraoperative hypotension was defined as a Mean Arterial Pressure (MAP) during surgery that was less than 30% of the preoperative level for at least 30 minutes. The relationship between intraoperative hypotension and POD incidence was adjusted for patient demographics and surgery-related factors. Results: Out of 428 male patients, 77 (18.0%) developed POD, and 166 (38.8%) experienced intraoperative hypotension. Surgery duration ≥ 300 minutes (OR = 1.873, 95% CI 1.041–3.241, p = 0.036), intraoperative hypotension (OR = 1.739, 95% CI 1.039–2.912, p = 0.035), and schooling (OR = 2.655, 95% CI 1.338–5.268) were independent risk factors for POD. The association between intraoperative hypotension and POD was significantly influenced by surgery duration (p for interaction = 0.008), with a stronger association in prolonged surgeries (adjusted OR = 4.902; 95% CI 1.816–13.230). Conclusions: Intraoperative hypotension and low education level are associated with an increased risk of POD in elderly male patients undergoing laryngectomy, especially with prolonged surgery duration.